The Evolution and Growth Dynamics of Sharia Pawnshops in Indonesia - Alfina Yuniar Prastika; Ahmad Reza; Febrianur Ibnu Fitroh Sukono Putra; Risanda Alirastra Budiantoro; Sisca Dian Rahmawati (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This research aims to elucidate and examine the dynamics of Islamic fiduciary services in Indonesia. Islamic economic system is very beneficial to the community now. Still, many must understand the differences between conventional and Islamic fiduciary services in concept and implementation. This paper uses the analysis method of a review of the literature to examine previous research relating to the history and development of Islamic fiduciary services in Indonesia. The results show that Islamic fiduciary services in Indonesia are close to Islamic idealism. It can be seen in terms of the fact that the system of financing, the cost of storage, the deadline for auction, and frequent misunderstandings between parties in Islamic fiduciary services with the public due to the need for adequate facilities from the Islamic fiduciary services. So, massive education is critical to increase the knowledge of the community in terms of that institution.